Effect of Zeolite Pre-Treatment on the Performance of a 7-Hole Catalytic Converter - Nur Fauziah; Yesi Angelia Simarmata; Iis Siti Jahro (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Rice husk ash is a promising silica source for zeolite X synthesis; however, studies comparing different pretreatment methods and their influence on catalytic converter performance remain limited. This study investigated the effect of bleaching and magnetic separation pretreatments on the properties of zeolite X synthesized from rice husk ash and its application in a 7-hole catalytic converter for vehicle exhaust emission reduction. The synthesized zeolite was characterized using XRF, FTIR, XRD, and SEM, while catalytic performance was evaluated based on changes in exhaust gas composition. Both pretreatment methods successfully produced zeolite X with SiO₂ and Al₂O₃ as the main framework components. However, bleaching pretreatment produced zeolite with higher crystallinity (73.39%), better crystal morphology, and a more favorable Si/Al ratio than magnetic separation. When applied in a 7-hole catalytic converter, the bleached zeolite achieved higher reductions of CO, HC, and CO₂ emissions by 65.50%, 67.07%, and 77.55%, respectively, compared to 51.61%, 69.95%, and 38.04% for the magnetic separation zeolite. These findings demonstrate that the pretreatment method significantly affects zeolite quality and catalytic converter performance, with bleaching pretreatment showing superior effectiveness for exhaust emission reduction.